Kur’ân’da Rics Kavramı - Dündar, Bahar Canset; Aydar, Hidayet (FSM Vakıf Üniversitesi)
Bu çalışmada, Kur’ân’da muhtelif bağlamlarda farklı anlam örgüleri içinde kullanılan “rics” kavramı üzerinde durulmaktadır. Sözlüklerde rics; pis, pislik, kötü iş, işkence, ceza, şüphe, gibi anlamları yanında ayrıca şirk, günah, azap, azaba götüren iş, öfke, vesvese gibi manalarda da kullanılmaktadır. Kumar oynamak, alkollü içki içmek, putlara tapmak, fal ile uğraşmak, ölü eti/leş, akmış kan ve domuz eti yemek gibi insana maddî ve mânevî zarar vererek onun hem fıtratını bozacak hem de iki cihan saadetini engelleyecek olan çirkin eylemler de Kur’ân’a göre “rics”tir. Kur’ân-ı Kerîm, münafıkları, kalplerinde hastalık olanları ve kâfirleri bozuk inançları sebebiyle “rics” olarak nitelediği gibi aşağılanmayı hak etmiş kişiler ve tiksinti uyandıran durumları da “rics” olarak tavsif etmektedir. “Rics” kavramı; burada kullanım şekilleri, anlamları, nüzul sebepleri ve ayetlerin muhatapları bakımından incelenmekte; barındırdığı manaları daha iyi anlamak açısından muhtelif tasnifler altında irdelenmektedir.

This study further elaborate the concept of “rijs” in different meanings within various aspects in the Qur’ān. Rijs; literary means dirtiness, abomination, nasty occupation, torture, punishment and doubt, besides, such meanings as polytheism, sin, punishment, an act that cause punishment, wrath and apprehension. In addition, nasty acts that cause both changing human’s nature and preventing the happiness of the world and the hereafter by damaging physically and spiritually is called “rijs” according to the Qur’ān, such as gambling, taking intoxicants, worshipping idolatry, playing fortune games, eating dead meat/ carrion, blood and pork. While the Qur’ān has described hypocrites, one in whose heart is a disease and those who reject Faith as “rijs” because of their wrong believes, also has qualified those who deserve to be insulted and abominable cases as “rijs”. In this article, the concept of “rijs” has been studied in respect to formal conceptual usage, meanings, conditions-reasons, and the addressee; and has been scrutinized beneath various classification in terms of comprehending more its meanings.
The Concept of Rijs in the Qur’ān
Keywords: Tefsir; Âyet; Rics; Kavram; Pislik; Tafsīr; Âya (verse); Rijs; Concepts; Abomination